ANALISIS STRUKTUR MAKRO PEMBERITAAN KASUS PROGRAM MAKAN BERGIZI GRATIS DALAM SURAT KABAR ONLINE KOMPAS.COM: ANALISIS WACANA KRITIS TEUN A. VAN DIJK - Nurul Fadilah; Ana Yuliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language in mass media plays an important role in shaping meaning and representing social reality through the discourse structures used in news texts. Reporting on the Free Nutritious Meal Program (MBG) published by Komoas.com is interesting to analyze because the media not only conveys information but also constructs reality through specific linguistic structures. This study aims to analyze the macro structure of news discourse related to the MBG program using Teun A. van Dijk’s critical discourse analysis approach. The research employed a descriptive qualitative method. The data consisted of three news articles about the MBG program published on Kompas.com. Data collection was conducted through documentation techniques, while data analysis focused on identifying the main topics and the organization of meaning within the news texts through macro structure analysis. The findings show that the macro structure of MBG news coverage tends to emphasize themes of program supervision, cases of student food poisoning, and criticism of the implementation system of the MBG program. The selected topics direct readers toward particular understandings regarding both the success and weaknesses of the policy implementation. Therefore, the macro structure in news discourse significantly influences public perception and demonstrates that media texts not only provide information but also represent certain ideologies and interests in constructing social reality.